Composition and antimicrobial activity of essential oils of Salvia fruticosa and Salvia ringens (Lamiaceae) - Stojanović, Danilo; Marčetić, Mirjana; Ušjak, Dušan; Milenković, Marina (Vojnosanitetski pregled, 2022)
Background/Aim. Plant essential oils (EOs) can have a significant antibacterial effect especially through additive or synergistic action as antibiotic adjuvants. We investigated the composition and activity of EOs of two species of genus Salvia (S) from Greece with the aim to determine their antimicrobial activity as well as the activity in combination with selected antibiotics. Methods. The aerial parts of wild-growing S. fruticosa and S. ringens were subjected to a steam distillation and the obtained EOs were analyzed by gas chromatography and gas chromatography/mass spectrometry. The broth-microdilution method was used in order to determine the minimum inhibitory concentrations (MICs) of EOs on seven strains of bacteria and one yeast. Antimicrobial activity of the combination of EO and antibiotics was investigated by checkerboard method and estimated by calculating fractional inhibitory concentration (FIC) of each component and fractional inhibitory concentration index (FICI). Results. Dominant component of S. fruticosa EO was trans-thujone (54.2%) and for S. ringens EO it was α-pinene (28.1%). The MICs of EOs of both species were in the range from 200 μg/mL to > 500 μg/mL. The strongest antimicrobial effect was achieved against Bacillus subtilis and Candida albicans. According to FICI values, EO of S. fruticosa had additive effect with ciprofloxacin against most of bacterial strains but not with amikacin. Conclusion. The essential oils of S. ringens and S. fruticosa showed modest antimicrobial activity. However, the essential oil of S. fruticosa showed a promising additive effect in combination with ciprofloxacin.